Badania wstępne nad wpływem podciśnienia na kłaczki osadu czynnego = Preliminary studies on the influence of negative pressure on activated sludge flocs - Gnida, Anna; Witecy, Dagmara (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
A sludge from municipal wastewater plant operated for biological contaminant removal was exposed to three different negative pressures (-200, -500 and -800 hPa) for three different duration times (30 second, 1 and 2 minutes). Sludge volume index, shear sensitivity of the sludge and activated sludge floc characteristic was the object of the study before and after negative pressure treatment. After the treatment the sludge settled better independently on the pressure value and duration time. The shear sensitivity changed the most when the pressure exposure of -800 hPa was 1 minute and longer. The flocs structure was more open after negative pressur and larger part of activated sludge was comprised by large flocs.
Keywords: podciśnienie; osad czynny; charakterystyka kłaczków; negative pressure; activated sludge; floc features